Influence Of Shadow And Shuttle Run Exercises On Badminton Sports Footwork Aged 13 - 15 Years At Pb Jaya Raya Jakarta - Wibowo, Febri Prasetyo Ari; Novita, Novita; Yudhaprawira, Asrori; Denatara, Eskar Tri; Candra, Juli (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
This study was conducted to determine the effect of shadow and shuttle run training on badminton footwork aged 13–15 years at PB Jaya Raya Jakarta. This study uses an experimental method that utilizes a two-group pretest-posttest design. The population studied in this study were PB athletes. Jaya Raya Jakarta has a population of 30 people. A purposive sampling method was used in the study, with the following criteria: At least 75% of players were on the attendance list during the last two months of training (actively involved in training); (2) Participants are PB athletes. (3) Age 13–15 years, (4) Male gender. The sampling test in the form of a foot movement agility instrument is a circuit-based leg exercise tester. The t-test was used in the analysis of the data. The results of the research are: (1) There is an effect of shadow training on the sports footwork of children aged 13–15 years in PB. Jaya Raya Jakarta, with t count 3,289 > t table 2.26 and a significance value of 0.009 0.05, resulting in an effect of 9.55%. (2) There is an effect of the shuttle run exercise on the badminton footwork of children aged 13–15 years in PB. Jaya Raya Jakarta, with a count of 4.155 > table 2.26 and a significance value of 0.002 0.05, resulting in an effect of 10.69%. (3) The shuttle run method is more effective for badminton footwork aged 13–15 years in PB Jaya Raya Jakarta than the shadow method.